Globalisation and Wage Inequality: A Comparison of the Manufacturing Sector in Canada and the United States from 1970 to 2001 - Grenier, Gilles; Tavakoli, Akbar (Journal of Income Distribution®, 2009)
This article compares Canada and the United States in terms ofthe evolution of the relative wages of production and non-productionworkers in the manufacturing sector. The results show that the wageratio is affected by similar economic globalisation variables in eachcountry. Other than technological changes, however, the overall effectof globalisation is more pronounced in Canada. Among economicglobalisation variables, such as technological changes and importsfrom developing countries, the latter has had a less harmful effecton low-skilled workers in the United States than those in Canada.Among the other variables, the wage gap is more affected by uniondensity in Canada. The impact of immigration is low in both countries.